Iron(II) and Iron(III) Complexes of Tridentate NNO Schiff Base‐like Ligands – X‐ray Structures and Magnetic Properties. Issue 24 (8th October 2018) - Dankhoff, Katja; Schneider, Sandra; Nowak, René; Weber, Birgit
Abstract : A series of new [Fe(L)2 ] iron(II) and [Fe(L)2 ] X iron(III) complexes is presented with varying tridentate NNO coordinating Schiff base‐like ligands (L – ) and different counterions ( X – = Cl –, Br –, I – BF4 –, PF6 –, and ClO4 – ) in the case of the iron(III) complexes. The crystal structures of one iron(II) and three iron(III) complexes are discussed, as well as the magnetic properties of the complexes regarding the possibility of the observation of spin crossover. While the three iron(II) complexes are predominantly high spin, in the case of the iron(III) complexes spin crossover was observed for the majority of the complexes (10 out of 12). Additionally, the optical properties and electrochemical behavior in solution was investigated and the results are compared with related systems from literature. Abstract :